1992
DOI: 10.1073/pnas.89.9.3917
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous glucocorticoids regulate an inducible cyclooxygenase enzyme.

Abstract: The effect of endogenous glucocorticoids on the expression of the cyclooxygenase enzyme was studied by contrasting cyclooxygenase expression and prostanoid synthesis in adrenalectomized and sham-adrenalectomized mice with or without the concurrent administration of endotoxin. Peritoneal macrophages obtained from adrenalectomized mice showed a 2-to 3-fold induction in cyclooxygenase synthesis and activity when compared to sham controls. Intravenous hj'ection of a sublethal dose of endotoxin (5 jzg/kg) further s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
192
3
3

Year Published

1993
1993
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 412 publications
(204 citation statements)
references
References 23 publications
5
192
3
3
Order By: Relevance
“…There is other possibility that the production of PGs is enhanced by increased COX-1 level mediated through some other growth factors, for example, interleukins or glucocorticoid. 47,48 In conclusion, we demonstrated that VMH lesioning induced intestinal cell hyperplasia but not hypertrophy, resulting in the enlargement of villi height. We also demonstrated that the gene expression of COX-1 in the intestine was enhanced in VMH-lesioned rats.…”
Section: Vmh Lesions In Jejunal Hyperplasiamentioning
confidence: 97%
“…There is other possibility that the production of PGs is enhanced by increased COX-1 level mediated through some other growth factors, for example, interleukins or glucocorticoid. 47,48 In conclusion, we demonstrated that VMH lesioning induced intestinal cell hyperplasia but not hypertrophy, resulting in the enlargement of villi height. We also demonstrated that the gene expression of COX-1 in the intestine was enhanced in VMH-lesioned rats.…”
Section: Vmh Lesions In Jejunal Hyperplasiamentioning
confidence: 97%
“…Inflammation results in an upregulation of the inducible COX-2 isoform of cyclo-oxygenase (Vane et al, 1994) which is readily induced by cytokines including IL-I (Maier et al, 1990). Indomethacin is relatively specific for COX-1 (Mitchell et al, 1993) while dexamethasone would be expected to prevent the protein synthesis-dependent induction of COX-2 during inflammation (Masferrer et al, 1992;Vane et al, 1994). In other words we should have blocked both the inducible and the constitutive forms of COX with the two treatments but failed in either case to modify substantially behavioural hypersensitivity, at least compared to anti-NGF.…”
Section: Discussionmentioning
confidence: 99%
“…These results reinforce the contribution made by mechanisms independent of NOS induction to the vascular hyporeactivity to NA. For instance, LPS induces an isoform of cyclo-oxygenase (COX-2) resulting in an enhanced formation of cyclo-oxygenase metabolites including vasodilator prostanoids (Masferrer et al, 1992). The subsequent enhanced formation of adenosine 3':5'-cyclic monophosphate (cyclic AMP) in the vascular smooth muscle and an impairment of the NA-mediated signal transduction (see Suba et al, 1992) (Szabo et al, 1993a).…”
Section: Tnf Prevents the Lps-induced Vascular Hyporeactivity To Nomentioning
confidence: 99%